Evaluation of cd44 and Pd-L1 expression during co-cultivation of tumor and hematopoietic stem cells - M. V. Bykova; A. A. Aktanova; I. P. Skachkov; V. V. Denisova; E. A. Pashkina (Онкогематология, 2025)
Background. Cd44 molecule is overexpressed on tumor‑associated cells, including stem cells, in the tumor microenvironment, which in most cases is a poor prognostic marker for the tumor progression. In addition, the pd‑L1 molecule positively correlates with Cd44, which is associated with resistance to antitumor therapy, so these markers are perspective targets for both diagnostics and therapy of oncological diseases.   Aim. To determine the expression of checkpoint molecules and Cd44 during co‑cultivation of tumor and hematopoietic stem cells under various conditions.   Materials and methods. Cd34+ hematopoietic stem cells (n = 10) and tumor lines 1301, K562 and SK‑mel37 were used for this study. Samples labeled with monoclonal antibodies to Cd44, pd‑L1 and pd‑1 were analyzed by flow cytometry.   Results. The expression of molecules was different with co‑culturing of hematopoietic stem cells with several types of tumors, so the number of Cd34+Cd44+ cells was 3 times lower in the group with SK‑mel37 compared to leukemia 1301 and K562 (the median was 7.1; 22.4 and 22.7, respectively). In addition, the expression of the pd‑L1 molecule on SK‑mel37 was significantly higher than on other tumor cells (p < 0.05).   Conclusion. It is necessary to study the patterns of change not only in the expression of these molecules, but also in co‑expression depending on the type and conditions of cells interaction with each other.